Influence of the acid erosion associated with dental bleaching in bovine enamel: In vitro study (Research, Society and Development, 2021)
Objective: To evaluate the influence of acid erosion caused by the daily intake of lemon juice or apple cider vinegar, associated with immediate dental whitening, on bovine enamel. Materials and Methods: 30 bovine teeth were sectioned to obtain enamel blocks and were distributed into three groups (n = 10): G1- Tooth whitening with 35% hydrogen peroxide; G2- Tooth whitening with 35% hydrogen peroxide + lemon juice and G3 - Tooth whitening with 35% hydrogen peroxide + apple cider vinegar. Treatments were performed for 21 days, the varnish was removed and the analysis of loss of structure and surface roughness were performed by means of non-contact 3D Confocal Chromatic Profilometer. The roughness data obtained were analyzed by Kruskal-Wallis and Mann-Whitney non-parametric tests. Results: All groups exhibited greater roughness (Sa) on the side exposed to the treatments (G1 = 3.17b; G2 = 4.17b; G3 = 3.99b) compared to the unexposed side (G1 = 2.55a; G2 = 3.94a; G3 = 2.40a). There was a statistically significant difference among the groups evaluated, being G1 (3.17A)